Respostas
respondido por:
2
3x^2-5x+2
∆= b^2-4ac
∆= (-5)^2 -4.3.2
∆= 25-24
∆= 1
X= -b+/-√∆
2a
X= -(-5)+/-√1
2.3
X= 5+/-1
6
X1= 5+1= 6/6= 1
X2= 5-1= 4/6= 0,666...
X1= 1
X2= 0,666...
Se vc quiser pode jogar na fórmula simplificada também que é:
x= -b+/-√b^2-4ac
2a
Que dá o mesmo resultado!
∆= b^2-4ac
∆= (-5)^2 -4.3.2
∆= 25-24
∆= 1
X= -b+/-√∆
2a
X= -(-5)+/-√1
2.3
X= 5+/-1
6
X1= 5+1= 6/6= 1
X2= 5-1= 4/6= 0,666...
X1= 1
X2= 0,666...
Se vc quiser pode jogar na fórmula simplificada também que é:
x= -b+/-√b^2-4ac
2a
Que dá o mesmo resultado!
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás